How trainee hospital doctors lead work-based projects. Issue 1 (10th December 2019) - Snelling, Iain; Benson, Lawrence Adrian; Chambers, Naomi
Abstract : Purpose: The purpose of this study is to explore how trainee hospital doctors led work-based projects undertaken on an accredited development programme in England. Design/methodology/approach: This is a case study of a leadership programme for hospital-based specialty trainees. The programme included participants leading work-based projects which were submitted for academic accreditation. Accounts of 35 work-based projects were thematically analysed to explore how participants led their projects. Findings: Leadership was often informal and based on a series of individual face-to-face conversations. The establishment of project teams and the use of existing communication processes were often avoided. The reasons for this approach included lack of opportunities to arrange meetings, fear of conflict in meetings and the personal preferences of the participants. The authors discuss these findings with reference to theory and evidence about conversations and informal leadership, highlighting the relevance of complexity theory. Research limitations/implications: The data are limited and drawn from the best accounts written for a specific educational context. There is therefore limited transferability to the leadership work of hospital-based specialty trainees in general. Future research into medical leadership might explore the micro practices of leadership and change, particularly in informal settings. Practical implications: Leadership development programmes for trainee hospital doctors might concentrate on developing skills of conversation, particularly where there are or may be perceived power imbalances. Exploring conversations within the theory of complex responsive processes should be considered for inclusion in programmes. Originality/value: This paper adds some detail to the general understanding of learning leadership in practice.